2010
DOI: 10.13083/reveng.v18i4.234
|View full text |Cite
|
Sign up to set email alerts
|

Uniformidade De Vazão De Fertilizantes Por Dosadores Helicoidais Em Função Do Nivelamento Longitudinal

Abstract: O objetivo deste estudo foi analisar o desempenho de dois tipos de mecanismos dosadores helicoidais de fertilizante, por transbordo e por gravidade, em função do nivelamento e da rotação do eixo de acionamento do dosador em fertilizantes mistura de grânulos e mistura farelada. Atualmente, o mecanismo dosador para fertilizante do tipo rosca sem-fim é oferecido como opção em aproximadamente 65,1% dos modelos de semeadoras-adubadoras disponíveis no mercado brasileiro, tendo seu desempenho pouco conhecido. Foi rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
2
2
0
2
Order By: Relevance
“…Equations 2and 4, which represent the behavior of the helical metering mechanism by longitudinal (M1) and lateral overflow (M3), respectively, showed similar variations relative to the inclination. Similar behavior was observed by Ferreira et al (2010), Franck et al (2015), and Garcia et al (2017), who reported that metering mechanisms with longitudinal or lateral overflows when subjected to positive (acclivity) and negative (declivity) longitudinal inclinations cause increases and decreases, respectively, in the application rate.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Equations 2and 4, which represent the behavior of the helical metering mechanism by longitudinal (M1) and lateral overflow (M3), respectively, showed similar variations relative to the inclination. Similar behavior was observed by Ferreira et al (2010), Franck et al (2015), and Garcia et al (2017), who reported that metering mechanisms with longitudinal or lateral overflows when subjected to positive (acclivity) and negative (declivity) longitudinal inclinations cause increases and decreases, respectively, in the application rate.…”
Section: Methodssupporting
confidence: 83%
“…Sowing is a practice that needs high precision, as it is one of the first stages within the production process of a given crop, being responsible for placing the seed and creating an environment for its development, and problems at this stage may not be reversed throughout the crop cycle (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2, 3, and 4 showed positive values for the longitudinal inclination estimator. It can be said that positive (upslope) and negative (downslope) longitudinal inclinations cause increases and decreases, respectively, in the fertilizer dosage, a fact that corroborates with Ferreira et al (2010) and Garcia et al (2017).…”
Section: Resultssupporting
confidence: 59%
“…Ao observar a tabela 1, notasse que não houve variação significativa no coeficiente de variação da distribuição linear de fertilizante entre as diferentes inclinações de trabalho impostas no dosador de rosca dupla, os valores obtidos ficaram em torno de 36% de variação, embora seja elevado, o dosador não varia com o relevo, fator que possibilita maior acurácia na qualidade na adubação em locais que possuem relevos acidentados. [2] demonstraram que todas as inclinações proporcionaram variação significativa na dosagem em função da inclinação longitudinal, tanto em dosador de rosca helicoidal por transbordo ou por gravidade, sendo submetidos a inclinações de 10º, 5º, 0º, -5º, -10º.…”
Section: Resultsunclassified
“…O ângulo de trabalho do dosador influencia na distribuição de fertilizante, principalmente em terrenos ondulados, como no caso do estado do Rio Grande do Sul -Brasil, assim, o tipo de dosador empregado, afeta a distribuição e a taxa de adubo dosado. Em estudo com diferentes tipos de dosadores de rosca helicoidal, trabalhando em diferentes inclinações longitudinais, [2] as inclinações utilizadas no estudo acarretaram em variação significativa na dosagem de fertilizante granulado. Outro parâmetro que tem influência na distribuição do fertilizante é a espaço que existe no interior do dispositivo dosador, entre a rosca helicoidal e o eixo de transmissão, [1] reduzindo esse espaço há melhoraria na distribuição de fertilizante.…”
Section: Introductionunclassified